Ecological effects of a long-term flood program in a flow-regulated river - Sabine Mannes; Christopher-Thomas Robinson; Urs Uehlinger; Thomas Scheurer; Johannes Ortlepp; Uta Mürle; Peter Molinari (Revue de Géographie Alpine)
The natural flow regime of many rivers on the globe has been altered by regulation, strongly influencing river morphology and aquatic biota. The incorporation of regimebased criteria such as flow and temperature regimes in restoration plans is an important step in river management. This paper summarizes the effects of a long-term flood program (15 floods over 8 years) on the river Spöl, Swiss National Park, on water physico-chemistry and river biota (periphyton, macroinvertebrates and fish). Due to hypolimnetic release, the floods had little impact on physical and chemical parameters. Periphyton biomass was reduced by the early floods and remained at low levels throughout the study period. Macroinvertebrate taxon richness, biomass and density were also significantly reduced and the macroinvertebrate assemblage shifted towards more disturbance-resistant taxa. The quality of fish habitat, especially for spawning, was noticeably improved by the floods. Further analysis suggested that the response of biota to floods of similar magnitude have changed over the study period in concert with the compositional shift in biotic assemblages.